ChemInform Abstract: Graphene‐Catalyzed Direct Friedel—Crafts Alkylation Reactions: Mechanism, Selectivity, and Synthetic Utility. Issue 20 (April 2016) - Hu, Feng; Patel, Mehulkumar; Luo, Feixiang; Flach, Carol; Mendelsohn, Richard; Garfunkel, Eric; He, Huixin; Szostak, Michal
Abstract: An efficient methodology for the alkylation of various arenes with styrene derivatives or benzylic alcohols is described.